Leptin alters somatosensory thalamic networks by decreasing gaba release from reticular thalamic nucleus and action potential frequency at ventrobasal neurons - Perissinotti, Paula Patricia (2018)
Leptin is an adipose-derived hormone that controls appetite and energy expenditure. Leptin receptors are expressed on extra-hypothalamic ventrobasal (VB) and reticular thalamic (RTN) nuclei from embryonic stages. Here, we studied the effects of pressure-puff, local application of leptin on both synaptic transmission and action potential properties of thalamic neurons in thalamocortical slices. We used whole-cell patch-clamp recordings of thalamocortical VB neurons from wild-type (WT) and leptin-deficient obese (ob/ob) mice. We observed differences in VB neurons action potentials and synaptic currents kinetics when comparing WT vs. ob/ob. Leptin reduced GABA release onto VB neurons throughout the activation of a JAK2-dependent pathway, without affecting excitatory glutamate transmission. We observed a rapid and reversible reduction by leptin of the number of action potentials of VB neurons via the activation of large conductance Ca 2+ -dependent potassium channels. These leptin effects were observed in thalamocortical slices from up to 5-week-old WT but not in leptin-deficient obese mice. Results described here suggest the existence of a leptin-mediated trophic modulation of thalamocortical excitability during postnatal development. These findings could contribute to a better understanding of leptin within the thalamocortical system and sleep deficits in obesity.